Real‐Time Seismogeodetic Earthquake Magnitude Estimates for Local Tsunami Warnings. Issue 1 (18th January 2023) - Golriz, Dorian; Hirshorn, Barry; Bock, Yehuda; Weinstein, Stuart; Weiss, Jonathan R.
Abstract: We estimate a seismogeodetic earthquake moment magnitude using unclipped, broadband velocity and displacement waveforms from collocated Global Navigation Satellite Systems and seismic stations located within 800 km epicentral distance for nine 7.2 < M w M_w < 9.1 earthquakes. We consider the vertical component of seismogeodetic displacement as an approximate source time function and integrate the associated time series to obtain the seismic moment. By continuing to integrate vertical displacement beyond the initial P ‐waves, we obtain rapid estimates of M w M_w that are within 0.2 magnitude units for 8 thrust faulting events and within 0.3 units for the single normal faulting event. Because our estimates of the seismic moment are based on the maximum value of integrated displacement, no regression against other source parameters, or distance, is necessary. Our new method shows promise for integration into earthquake and local tsunami early warning systems, including tsunami earthquakes characterized by relatively slow moment release over a longer rupture time, and earthquakes with complex source time functions. Plain Language Summary: Tsunami Warning Centers are responsible for alerting coastal populations of expected tsunami waves caused by significant earthquakes. Traditionally, warnings rely on rapid magnitude estimation based on distant seismic data. This is sufficient for ocean‐wide tsunami warnings but often not for coastal populations closest to a causative earthquake. More timely warnings for local tsunamis can be obtained by supplementing measurements of seismic accelerations with displacements from Global Navigation Satellite Systems instruments located close to the earthquake source. In this study, we use this data combination to estimate the magnitude of nine historical earthquakes around the Pacific basin. Our real‐time simulations show that we can obtain useful and reliable magnitude estimates for large earthquakes and issue local tsunami warnings within minutes after rupture initiation. Key Points: Combined seismic and geodetic (seismogeodetic) data enable rapid earthquake magnitude estimates Seismogeodetic magnitude estimates for very large earthquakes are timelier than those based on seismic data alone The seismogeodetic method is applicable to earthquakes with complex source mechanisms, including tsunami earthquakes